Word searches in second language conversation: talk and nonverbal as interactional resources - Abdullah, Nur Nabilah (IIUM Press, International Islamic University Malaysia, 2017)
Studies on face-to-face interactions have demonstrated how spoken language involves not only verbal but also a mutual collaboration with nonverbal resources. Nonverbal such as gaze, gestures, body posture and physical movement are part and parcel of the details of ordered social interaction, and they can be significant resources in interaction (Hazel et al., 2014). This study has investigated the nonverbal resources displayed in word search phenomenon in second language conversation. Word search is regarded as a type of self-initiation repair in which the progressivity of the speaker’vs turn is momentarily ceased due to an item (i.e. word) is not available to the speaker when due (Schegloff et al., 1977). The context of the study is a non-educational context (Firth and Wagner, 1997; Firth and Wagner, 2007; Gardner and Wagner, 2004) where casual conversation among international university students having dinner at a cafe is recorded. This study examines conversations between international students communicating in English as it is the most common language that international students resort to when speaking with someone who has a different language background. Using Conversation Analysis (CA), this study aims to explore talk and nonverbal resources in word search sequences. The findings from the investigation suggest that there is a relationship between talk and embodied actions in word search sequences among second language speakers.